Comparative efficacy and safety of the novel oral anticoagulants dabigatran, rivaroxaban and apixaban in preclinical and clinical development - Ufer, Mike (Thrombosis and Haemostasis, 2010)
Therapeutic oral anticoagulation is still commonly achieved by administration of warfarin or other vitamin K antagonists that are associated with an untoward pharmacokinetic / pharmacodynamic (PK/PD) profile leading to a high incidence of bleeding complications or therapeutic failure. Hence, there is an unmet medical need of novel easy-to-use oral anticoagulants with improved efficacy and safety. Recent developments include the identification of non-peptidic small-molecules that selectively inhibit certain serine proteases within the coagulation cascade. Of these, the thrombin inhibitor dabigatran and factor Xa inhibitor rivaroxaban have recently been licensed for thromboprophylaxis after orthopaedic surgery mainly in Europe. In addition, the factor Xa inhibitor apixaban is in late-stage clinical development. Each drug is prescribed at fixed doses without the need of anticoagulant monitoring. Phase III trials in orthopaedic patients essentially resulted in non-inferior efficacy of dabigatran and superior efficacy of rivaroxaban over enoxaparin without any marked differences of drug safety, while apixaban data is still controversial. However, alterations of rivaroxaban and apixaban pharmacokinetics upon interactions with inhibitors and inducers of CYP3A4 or P-glycoprotein may complicate the use of these compounds in daily practice, whereas dabigatran elimination largely depends on renal function. Hence, this review reports PK/PD, efficacy and safety data of dabigatran, rivaroxaban and apixaban throughout preclinical and clinical development.
Keywords: Clinical trials; oral anticoagulants; venous thrombosis; pharmacodynamics; pharmacokinetics; drug design